Pediatric dermatology - Cohen, Bernard A. (Elsevier, 2022)
Diagnostic algorithms, high-quality illustrations, and concise, easy-to-navigate text written by a leading authority in the field set this text/atlas apart, making it ideal for clinical use as well as board exam preparation. Contains nearly 1,000 superb photographs (100 are new or updated) balanced by clear and succinct text. Keeps you up to date with the most current knowledge and latest advancements in the field, including new variants of conditions for infantile hemangiomas and vascular malformations and approaches and findings for treating pigmented lesions in infants and children. Features numerous summary tables and differential diagnosis algorithms to help simplify diagnosis. Enhanced eBook allows you to access all of the text, figures, and references from the book on a variety of devices.